2001
DOI: 10.1063/1.1378317
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and dynamics of I2(B)–Ne

Abstract: The I2–Ne complex has been examined using double resonance and fluorescence depletion techniques. Action spectra for I2(B,v)–Ne, detected by monitoring the I2(B,v−1) predissociation fragments, show that the Δν=−1 predissociation channel is less efficient for levels above v=32 (with no excitation of the intermolecular vibrations), and closed for v>36. From these data we obtained a revised estimate for the dissociation energy for I2(B)–Ne of D0=57.6±1.0 cm−1. Action spectra for I2(B,v=34)–Ne, detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
56
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 51 publications
14
56
0
Order By: Relevance
“…The first experiments on van der Waals (vdW) clusters consisting of a dihalogen molecule and rare-gas atoms have been performed by Levy et al, 1,2 followed by a large number of studies on systems such as He n I 2 (n=1-3), 3,4 Ne n I 2 (n=1-6), 2,5,6 Ne n Br 2 , 7 Rg 1,2 X 2 (Rg=He, Ne, Ar and X=Cl, Br), [8][9][10][11] Ne n ICl (n=1-5), 12,13 He n ICl ((n=1-3). 14,15 More recently the interest in studying such species has been intensified due to additional experiments, rotational, and infrared spectroscopy on doped helium nanodroplets, [16][17][18] and on small/intermediate-sized doped helium clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The first experiments on van der Waals (vdW) clusters consisting of a dihalogen molecule and rare-gas atoms have been performed by Levy et al, 1,2 followed by a large number of studies on systems such as He n I 2 (n=1-3), 3,4 Ne n I 2 (n=1-6), 2,5,6 Ne n Br 2 , 7 Rg 1,2 X 2 (Rg=He, Ne, Ar and X=Cl, Br), [8][9][10][11] Ne n ICl (n=1-5), 12,13 He n ICl ((n=1-3). 14,15 More recently the interest in studying such species has been intensified due to additional experiments, rotational, and infrared spectroscopy on doped helium nanodroplets, [16][17][18] and on small/intermediate-sized doped helium clusters.…”
Section: Introductionmentioning
confidence: 99%
“…14 and 15) and Ne-I 2 (Ref. 16) by the groups of Klemperer and Heaven. From a theoretical perspective, ab initio high level calculations have also predicted the existence of a double-minimum a) E-mail: kalemos@chem.uoa.gr.…”
Section: Introductionmentioning
confidence: 99%
“…The energy resolution of the spectra from which the I 2 vibrational distributions were obtained was of 0.3 cm -1 line width. 12 With this spectral resolution Heaven and co-workers 12 found no population of the I 2 (B,V f )36) fragment, and from this absence they concluded that the ∆V ) -1 channel is closed for V ) 37. Thus, the theoretical result of zero I 2 (B,V f )36) population for energies E up to 0.5 cm -1 higher than the V ) 37 resonance energy is consistent with the experimental absence of I 2 (B,V f )36) population when I 2 (B,V)37)-Ne energies higher than the resonance energy up to 0.15 cm -1 (half the spectral resolution line width) are probed.…”
Section: Resultsmentioning
confidence: 95%
“…12 It is stressed that in the present dynamical calculations dissociation of the I 2 (B)-Ne complex occurs only via vibrational predissociation. The implication is that suppression of the ∆V ) -1 predissociation channel is only due to the vibrational predissociation dynamics occurring in the B electronic state, without the need to invoke the influence of electronic predissociation.…”
Section: Resultsmentioning
confidence: 99%